Analysis Research Trends on Barriers to Halal Label Registration in Indonesia: A Literature Review - Natsir, Imron; Triastuti, Eny (Universitas Nahdlatul Ulama Blitar, 2024)
This research investigates research trends related to obstacles in registering halal labels in Indonesia. This research is a literature review. The analysis uses a systematic literature review method. Data sources include journal articles, research reports and government publications from 2019 to 2024. A literature search was carried out through major academic databases with relevant keywords, followed by a selection and synthesis process of the data obtained. The search is carried out with the help of the Publish or Perish program. Through an in-depth literature review, this study identifies the main factors that hinder the halal registration process and evaluates their impact on various stakeholders. The obstacles identified include costs, bureaucratic complexity, awareness and understanding of business actors, and the capacity of halal certification institutions. These findings offer insights that can help stakeholders formulate effective interventions to increase the number of halal label registrations, which is crucial for meeting domestic and global market needs and increasing the competitiveness of Indonesian products.